Pertanggungjawaban Rusia dan Ukraina terhadap Penyerangan Pembangkit Listrik Tenaga Nuklir (Nuclear Power Plant) Zaporizhzia selama Konflik Bersenjata dalam Perspektif Hukum Internasional - Barbara Britny Bele Bau; Elisabeth N S B Tukan; Gerald A Bunga (Artemis Law Journal, 2026)
The attacks on the Zaporizhzia Nuclear Power Plant during the conflict between Russia and Ukraine, bring the world closer to nuclear accident. Russia successfully took control of this nuclear power plant, resulting in ongoing attacks and military activities around the facility. Both Russia and Ukraine accuse each other and refuse to acknowledge the mastermind behind the attack on the ZNPP. The research problem in this study is what is the responsibility of Russia and Ukraine regarding the attack on the ZNPP. The purpose of this research is to exemine, analyze, explain, and determine the accountability that can be imposed on Russia and Ukraine for the attack on the ZNPP. This research is normative juridical study conducted on the General Library of Nusa Cendana University, Kupang. There are books of humanitarian and international accountability that the author obtained there, which serve as references during research. Based on research findings, it has been determined that the attack on the ZNPP is clear violation of international law, particularly the rules of war outlined in the 1949 Genewa Conventions and additional protocol I of the 1977 Genewa Conventions. As a result, international accountability can be pursued through the Responsibility of State for Internationally Wrongful Acts Convention 2001. It would be better for Rusia and Ukraine to comply with international regulations, so nuclear at the Zaporizhzia Nuclear Power Plant is maintained and to immediately fulfill the forms of international accountability in accordance with applicable regulations.